Potencial de redução de sódio em copa suína - Di Domenico, Jocasta (2019)
The growing increase in diseases caused by excessive salt consumption led the Ministry of Health together with the food industries to list some measures to reduce the high levels of sodium. These measures cover a large number of foods. The canopy is a cured inlay, obtained from the porcine super pallet, which goes through the salting process and resalga with the use of common salt and healing salts. This sausage is not yet part of the salt reduction agreement, however this food contains sodium chloride in high concentrations, which promotes the conservation and is highly responsible for the sensorial characteristics of the product. The aim of the present study was to reduce sodium content without interfering with canopy acceptance, through NaCl direct reduction methods, partial NaCl replacement with KCl and reduction of salting time. Six treatments were carried out, Standard with 2 days of salting and 5 days of salting. The other treatments T1 with 70% of NaCl and 30% of KCl, T2, T3, T4 with 85% NaCl and 15% of KCl, T5 with 100% of NaCl, with 2 days of salting and 2 days of salivation. These treatments were evaluated in relation to the alterations of the microbiological, physical-chemical and sensorial characteristics. It was verified that all the treatments met the current legal standards and presented no significant difference in acceptance. The treatment with the lowest sodium content was the T5 treatment, in which it was possible to reduce the sodium content by up to 50%.